Knowledge Management dalam Implementasi Green Supply Chain di Industri Manufaktur (Studi Kasus PT XYZ) - Melia Handayani; Rubby Rahman Tsani; Syifa Fajar Maulani; Siti Annisafa Oceania; Narantaka .; Ira Nirmala; Deri Hendriawan (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
The rapid growth of Indonesia’s industrial sector has intensified sustainability demands, yet empirical studies integrating Knowledge Management (KM) as a driver of Green Supply Chain Management (GSCM) in Indonesian manufacturing firms remain limited. This study aims to analyze the relationship and causal effect of KM on GSCM implementation at PT XYZ. A mixed-method approach was employed combining descriptive quantitative and qualitative research. The population comprised all SCM Division employees at PT XYZ, with 16 selected through purposive and census sampling. Primary data were collected via a 20-item, 4-point Likert scale questionnaire and in-depth interviews with the SCM Division Head; secondary data came from company documents. Quantitative data were analyzed using descriptive statistics, Pearson correlation, and simple linear regression at the 5% significance level, while qualitative data validated all findings through method triangulation. Results show a strong positive correlation between KM and GSCM (r = 0.63; p < 0.05) and a significant causal effect (β = 0.57; R² = 0.39), with KM accounting for 39% of GSCM implementation variance. KM and GSCM at PT XYZ have a strong positive relationship, and KM significantly influences GSCM implementation. Companies should strengthen KM through knowledge-sharing and continuous training to accelerate green supply chain adoption.